Absorption study of triangular and rectangular slotted on hollow pyramidal absorber / Mohamad Faisal Asmadi ... [et al.] - Asmadi, Mohamad Faisal; Abdullah, Hasnain; Fazin, Mas Izzaty; Razali, Ahmad Rashidy; Taib, Mohd Nasir; Ahmad, Azizah; Mohamad Noor, Norhayati (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Today, electromagnetic wave theory is commonly used in many engineering devices. However, such devices produce electromagnetic (EM) radiation, damaging people’s health and the impact of other electronic device’s operation. Therefore, Microwave Absorber has been widely used in anechoic chamber to measure equipment radiation and prevent unwanted radiation and electromagnetic interference. This research investigates the absorption performance of pyramidal absorbers with a slotted method design. This research used rectangular and triangular slotted on the hollow pyramidal absorber. There are six types of slotted: Design 1, Design 2, and Design 3 which have triangular shapes, and Design 4, Design 5, and Design 6, have rectangular shapes. The pyramidal absorber is produced using CST Microwave Studio Suite. Afterward, the fabrication process is performed using cardboard and coated with Powdered Activated Carbon (PAC). Measurement had been done successfully via far-field measurement using an arch method at 1 GHz to 12 GHz. The slotted pyramidal absorber’s absorptivity was taken in each frequency band and was tabulated in figure 10. The result is compared with their maximum absorption in each of the four frequency bands. Comparison based on slot design, triangular and rectangular each had its own advantages at a certain frequency. However, small rectangular slot of Design 1 shows consistent absorption performance at all frequency band